1986
DOI: 10.1002/bit.260280702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microorganisms on rate of liquid extraction of ethanol from fermentation broths

Abstract: Liquid extraction is one means of removing metabolic products continuously during a fermentation and so reducing product inhibition. It is known that microbial organisms are attracted to liquid-liquid interfaces, and it is important for the design of extraction systems to establish if this has a detrimental effect on the rate of extraction. The extraction of ethanol from aqueous suspensions of yeast (Saccharomyces cerevisiae) using n- decanol is described in this paper. It was found that the presence of the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…Indeed, the yeast cells were observed by light microscopy to adhere to the surface of dodecanol droplets; a similar yeast adhesion to another aliphatic alcohol decanol has recently been reported. 16 A relationship between cell killing and cell attraction is further supported by the fact that dibutylphthalate, which does not attract yeast cells, was, in the present study, found to be non-toxic. A further correlation can be made between phase toxicity and solvent polarity.…”
Section: 1 Yeast Growth In Alcohol-saturated Brothssupporting
confidence: 80%
“…Indeed, the yeast cells were observed by light microscopy to adhere to the surface of dodecanol droplets; a similar yeast adhesion to another aliphatic alcohol decanol has recently been reported. 16 A relationship between cell killing and cell attraction is further supported by the fact that dibutylphthalate, which does not attract yeast cells, was, in the present study, found to be non-toxic. A further correlation can be made between phase toxicity and solvent polarity.…”
Section: 1 Yeast Growth In Alcohol-saturated Brothssupporting
confidence: 80%
“…This effect may be explained by the formation of multilayers of biomass, which would not affect the interface, but may affect transport through the interfacial region. In a previous study (Crabbe et al, 1986) the effect of yeast cells on extraction of ethanol was investigated. They found that the biomass caused a reduction in mass transfer at similar concentrations to those studied here.…”
Section: Biomassmentioning
confidence: 99%
“…Crabbe et al (1986) investigated the effect of yeast cells on transfer rates of ethanol from water into n-decanol; an 86% reduction in transfer rates was observed at a concentration of 0.1 g/l of yeast cells. This reduction was attributed to physical blocking of the liquidliquid interface by adsorption of cells.…”
Section: Introductionmentioning
confidence: 99%
“…The simple mechanisms involve blockage of the interfacial area available for mass transfer due to cell's absorption at the liquid-liquid interface, increase of the interfacial rigidity through absorption of interfacially active components of the fermentation broth, etc. Crabbe et al (1986) noted the substantial reduction in the rate of ethanol extraction from the fermentation broth compared with the pure system due to the absorption of yeast cells at the liquid-liquid interface. Similarly, Eldridge et al (1989) attributed a considerable decrease in mass transfer efficiency to the reduction of internal circulation in droplets due to the effect of surface-active agents in the broth.…”
Section: Modeling and Optimizationmentioning
confidence: 99%